Constructing the sense of self in psychosis using the amniotic therapy: a single case study. Issue 3 (3rd July 2019) - Germani, Alessandro; Ambrosecchia, Marianna; Buratta, Livia; Peciccia, Maurizio; Mazzeschi, Claudia; Gallese, Vittorio
ABSTRACT: Some people diagnosed with "schizophrenia" showed a fundamental alteration of the sense of self. From a psychodynamic perspective, it has been hypothesized that patients diagnosed as schizophrenic have disorders of the embodied self and its boundaries. Phenomenologically, it has been observed a self-disorder, at an implicit and pre-reflective level of bodily awareness. Neuroscientific evidence seems to confirm the aforementioned aspects. The mean levels of Interoceptive Accuracy (IA), which is an objective empirical measure of interoception, namely a measure of basic awareness distinct from subjective measures, are significantly lower in patients with a diagnosis of schizophrenia than among healthy controls. Affiliative touch is crucial for constructing a basic sense of self and its boundaries, and it affects interoception. In order to reduce the disturbance of the sense of self, Angelo participated for three years in an experimental intervention plan including Amniotic Therapy (AT) and individual psychodynamic psychotherapy. AT is a group-therapy based on sensory-motor interactions, especially affiliative touch, similar to those involved in "holding". Results showed an increase in the Angelo's IA and global functioning, as well as a significant decrease in positive symptoms. In Angelo, AT seems to strengthen a basic sense of self, reducing self-disorder.